Kewenangan Lembaga Swadaya Masyarakat sebagai Pengawas Eksternal Berkaitan dengan Pengelolaan Anggaran Pendapatan dan Belanja Desa Mlirip, Kecamatan Jetis, Kabupaten Mojokerto - Hanim Faizah; Subekti Subekti; Ernu Widodo (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This thesis discusses the authority of Non-Governmental Organizations (NGOs) as external supervisors in the management of the Village Revenue and Expenditure Budget (APBDes) in Mlirip Village, Jetis District, Mojokerto Regency. The purpose of this study is to analyze the extent of the role of NGOs in supervising the management of village budgets, as well as to evaluate the effectiveness and obstacles faced by NGOs in carrying out their supervisory functions. This study uses a qualitative approach with a case study method, involving interviews, observations, and document analysis related to village budget management in Mlirip Village. The results of the study indicate that NGOs have the authority to supervise the planning, implementation, and accountability of the APBDes through various supervisory mechanisms, such as social audits, counseling, and advocacy. However, in practice, NGOs face various obstacles, including lack of community participation, limited resources, and bureaucratic obstacles. Nevertheless, the role of NGOs as external supervisors remains important to encourage transparency and accountability in village budget management, as well as to ensure that the village budget is used in accordance with the needs and objectives that have been set. This study is expected to contribute to the development of more effective village budget supervision mechanisms in the future. Keywords: , , ,,.